Colistin Therapy in a 23-Week Gestational-Age Neonate with Multidrug-Resistant Acinetobacter baumannii Pneumonia - Lulic-Botica, Mirjana; DeJesus, Lilia (American Journal of Perinatology Reports, 2011)
Multidrug-resistant pathogens are becoming more difficult to treat with significantly increasing infection rates. The lack of new antibiotics to combat these strains has led to the resurgence of older antibiotics. This case highlights the first reported use of colistimethate sodium treatment in a 23-week gestational-age neonate with multidrug-resistant Acinetobacter baumannii pneumonia who developed acute renal failure and seizures shortly after initiation of treatment.
Keywords: Colistimethate; neonate; extremely low-birth-weight; multidrug resistant